2002
DOI: 10.1002/ijc.10809
|View full text |Cite
|
Sign up to set email alerts
|

A cleavable adapter to reduce nonspecific cytotoxicity of recombinant immunotoxins

Abstract: One of the problems associated with the administration of immunotoxins is hypersensitivity reaction such as vascular leak syndrome. This may be prevented by decreasing the plasma half-life. To improve immunotoxins with respect to reduced side effects, we have previously described the development of a cleavable adapter. This adapter links the toxic moiety and ligand that are usually directly coupled. In our study, the cytotoxicity of saporin linked either directly or via the adapter to epidermal growth factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 23 publications
(24 reference statements)
1
50
0
Order By: Relevance
“…11 and in anticancer therapy, to construct immunotoxins or ligand toxins [18][19][20][21] and SAP complementary DNA (cDNA) has been used for expressing targeted recombinant chimeras. 17,[22][23][24][25] When a SAP-based secretory chimera was expressed in Xenopus laevis oocytes, total inhibition of cellular protein synthesis was observed that could be restored only by supplementing neutralizing anti-SAP antibodies into the oocyte cytosol, 26 indicating that, although almost all of the chimera was secreted, the few molecules escaping from the secretory pathway were sufficient to inactivate protein synthesis in the host cells.…”
mentioning
confidence: 99%
“…11 and in anticancer therapy, to construct immunotoxins or ligand toxins [18][19][20][21] and SAP complementary DNA (cDNA) has been used for expressing targeted recombinant chimeras. 17,[22][23][24][25] When a SAP-based secretory chimera was expressed in Xenopus laevis oocytes, total inhibition of cellular protein synthesis was observed that could be restored only by supplementing neutralizing anti-SAP antibodies into the oocyte cytosol, 26 indicating that, although almost all of the chimera was secreted, the few molecules escaping from the secretory pathway were sufficient to inactivate protein synthesis in the host cells.…”
mentioning
confidence: 99%
“…Saporin and saporin-EGF were cloned previously [14]. All proteins were expressed in Escherichia coli Rosetta DE3 pLys (Novabiochem, Schwalbach, Germany) and isolated by Nickelnitrilotriacetate chromatography as described elsewhere [15].…”
Section: Expression Of Proteinsmentioning
confidence: 99%
“…Regardless of the endosomal escape mechanism, drugs that exert their effect inside the cytosol or in organelles should accumulate suitably within the cell to achieve maximum toxicity. A promising strategy to achieve intracellular trapping is the inclusion of a cleavable peptide that, once cleaved inside the cytosol, converts the drug to a membrane-impermeable protein by removing any motif or domain used for membrane translocation [46,47]. An analogous procedure describes the insertion of a natural organelle-specific cleavage recognition site of the mitochondrial malate dehydrogenase signal sequence.…”
Section: Endosomal Escapementioning
confidence: 99%